Studi Eksperimen Penggunaan Metode Bermain Peran Terhadap Pemahaman Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam Di Kelas VIII MTs An-Nashr Tarogong Kaler Garut - Maria, Anly; Noer, Gina Valentina (STAI Al-Musaddadiyah Garut, 2025)
Understanding is defined as the level of understanding of a student taking lessons given by a teacher or being able to understand something after something can be known and remembered. So far, students' understanding of Islamic Cultural History subjects is still low, from the results of student tests as many as 46% of students have not met the KKM (Minimum Criteria Completeness), this can be caused by a lack of variety of methods. Therefore, it is necessary to innovate varied learning methods, such as using the role-playing method is a learning method that involves students directly to act out a story in real life.The purpose of this study was to describe the effect of the role-playing method on student understanding of Islamic Cultural History subjects. The research method uses quantitative experiments. Data collection techniques by means of observation, tests and documentation studies. While data processing using statistical data analysis. The results showed that the average pretest of the experimental class was 71.9 after being treated with the role-playing method, the average posstest value increased to 90.4, while the average pretest value of the control class was 72.4 after being given treatment that did not use the role-playing method, the average posstest value was 80.1. based on the results of hypothesis testing, the posstest results of the experimental class and control class obtained Thitung (4.348) and Ttabel (2.001) with db = 58, then Thitung = 4.348 < Ttabel = 2.001. So it can be concluded that there is an effect of the role-playing method on student understanding of Islamic Cultural History material in class VIII Mts An-Nashr Tarogong Kaler Garut. Keywords: Role-playing method, Student Understanding, Islamic Cultural History.